Systemic modelling of soil water thermodynamics under natural conditions of air temperature and pressure - Braudeau, Erik (European Journal of Applied Sciences, 2020)
Following the recent theorization of the systemic approach of natural organizations such as soils, we give in this article the systemic definition of three fundamental variables of thermodynamics: temperature as the internal energy of molecules constituting a fluid phase “ ; entropy ( ), as the ratio of two organization variables of the phase that are: the occupational volume of molecules and their own volume in the phase of volume ; and the internal molecular chemical potential as the ratio of the temperature of a molecule to its mass . This allowed the following conceptual advances that could not be done using the two principles of thermodynamics: i) establishing the definitional equations of the 3 equivalent forms of the Gibbs free energy of the system, ii) establishing that the general equilibrium criterion of the system is the internal molecular potential rather than the temperature , iii) removing the confusion between internal and external pressures of the system that did not allow to distinguish the two types of energy of a molecule: internal and external , then iv) correcting accordingly the differential equations of thermodynamic potentials as well as the Gibbs-Duhem equation. Application to the soil water air system is given followed by some comments about this new vision of thermodynamic equilibrium modeling.